Short- term load forecasting using an artificial neural network / Hafiz Hafifi Abdullah - Abdullah, Hafiz Hafifi (2012)
This report represent the short-term load forecasting (STLF) using an artificial neural network (ANN). Load forecasting is very important for planning and operation of electric utility. STLF can give one hour a head energy load forecasted.